ISOLATION AND IDENTIFICATION OF BACTERIA FROM GOAT MILK PERANAKAN ETAWA INDICATED CLINICAL MASTITIS IN SEVERAL S - Isnan, M Hasan; Gelgel, Ketut Tono Pasek; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2017)
The purpose of this study was to determine the types of bacteria as a cause of clinical mastitis in goats Peranakan etawa in Banyuwangi. In this study, the sample used goat milk peranakan etawa in District Pesanggaran, Rogojampi, Songgon and Srono in Banyuwangi. As many as 11 samples were  taken then analyzed in Laboratory Microbiology, Faculty of Veterinary Medicine Udayana University. Phase isolation and identification of samples were done to identify the bacteria that cause clinical mastitis through several stages of growth on Sheep Blood Agar (SBA), Gram stain, catalase test, test oxidase, growth in the TSIA and continued test Indol, Methyl Red, Voges Proskauer and citrate (IMViC ). Based on the results, namely mastitis-causing bacteria; Staphylococcus sp, Pseudomonas sp, Neisseria sp, E.coli, Corynebcaterium sp and Listeria sp. The conclusion of this study disease mastitis in goats Peranakan etawa in the District of Bayuwangi caused by Staphylococcus sp, Pseudomonas sp, Neisseria sp, E.coli, Corynebcaterium sp and Listeria sp.
Keywords: Mastitis klinis; isolasi; bakteri